2016
DOI: 10.7717/peerj.1656
|View full text |Cite
|
Sign up to set email alerts
|

Performance of women with fibromyalgia in walking up stairs while carrying a load

Abstract: Background. Fibromyalgia is a chronic disease characterized by widespread pain and other associated symptoms. It has a relevant impact on physical fitness and the ability to perform daily living tasks. The objective of the study was to analyze the step-by-step-performance and the trunk tilt of women with fibromyalgia in the 10-step stair climbing test compared with healthy controls.Methods. A cross-sectional study was carried out. Twelve women suffering from fibromyalgia and eight healthy controls were recruit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Participant had to climb as fast as possible 10-step stair. This test was previously used as a physical test in fibromyalgia patients [2527] with excellent reliability (ICC = 0.972). [27]…”
Section: Methodsmentioning
confidence: 99%
“…Participant had to climb as fast as possible 10-step stair. This test was previously used as a physical test in fibromyalgia patients [2527] with excellent reliability (ICC = 0.972). [27]…”
Section: Methodsmentioning
confidence: 99%
“…[ 10 14 ] In 2 studies, women with FM had to climb 10 steps either empty handed or carrying a load. [ 12 , 13 ] In the first of these studies, the performance in the stair ascent was assessed to evaluate the effects of a training program aimed at proving that physical exercise prevents progressive loss of performance in this task. [ 13 ] The second focused on detecting differences in motor patterns between women with FM and healthy controls while using stairs.…”
Section: Introductionmentioning
confidence: 99%
“…[ 13 ] The second focused on detecting differences in motor patterns between women with FM and healthy controls while using stairs. [ 12 ] Three other studies utilized a test involving stair ascent to compare the performance and/or response of FM patients and healthy controls to a training program. [ 10 , 11 , 14 ] All 3 studies concluded that patients with FM needed more time to complete the stair climbing task.…”
Section: Introductionmentioning
confidence: 99%
“…Fourth, we considered the evaluation of pain in this study. Patients with pain symptoms are generally thought to experience different types of pain, such as spontaneous pain ( Nagakura et al, 2019 ; Tanei et al, 2020 ), pain during joint motion ( Avila et al, 2014 , 2017 ), pain on load ( Collado-Mateo et al, 2016 ), and noxious stimulus-evoked pain. The pain experienced by FM patients may comprise all the pain types mentioned above.…”
Section: Discussionmentioning
confidence: 99%